Simulator-mediated learning: enhancing accounting teaching-learning processes in higher education - Diana Gaviria; Juan Arango; Alejandro Valencia-Arias; Lemy Bran-Piedrahita; Ángel Marcelo Rojas Coronel; Alejandra Romero Díaz (Cogent Education, 2024)
AbstractThe literature has identified a significant dropout of students at the transition from high school to higher education, especially in areas related to mathematics. Therefore, new didactic tools have been identified to help teachers in the process of knowledge transfer, as simulators are an increasingly popular tool in their integration into educational environments. However, there is a lack of relevant research on the use of simulators in accounting education, which underlines the need for this study in a little explored area. For this reason, a study was conducted to analyze the impact perceived by university students in the city of Medellin on the use of a simulator to calculate the depreciation rate of assets. This was an exploratory study with a mixed approach, in which 45 students from a public university in the city participated. The results reflect the positive effects of the use of simulators in the classroom, such as consolidation of knowledge, agility in performing application exercises and better understanding of the content, allowing the conclusion that these technologies effectively mediate the teaching-learning processes in higher education. The study demonstrated the positive impact of simulator-mediated learning in higher education for the teaching of accounting subjects, with a high level of acceptance by students, increasing student motivation, content comprehension, and participatory behavior in the classroom. Although the study highlights the effectiveness of simulators as a teaching tool, it also indicates the need for further research on issues such as implementation costs and affective impact.